Microcontroller – Based H2S Detector Using MQ136 and SMS Gateway - Pradana, Arvian Satya; Fadlilah, Umi (Aceh Journal of Electrical Engineering and Technology, 2025)
Hydrogen Sulfide (H2S) is a toxic gas that can endanger humans at high levels. Therefore, developing an H2S gas detector is crucial for environmental safety and human health. This study developed an H2S gas detection device using Arduino that provides notifications via SMS. The device uses an MQ-136 gas sensor as the main component to detect H2S gas concentration in the air. The Arduino Uno microcontroller processes data from the sensor and displays gas concentration on a 20x4 LCD screen. For easy information dissemination, the SIM900A module sends SMS notifications every minute and when there is a change in gas concentration. Sensor calibration techniques were implemented to ensure optimal H2S gas accuracy, with field tests showing an error rate of 0.21% for the MQ-136 sensor readings. The device is also equipped with a buzzer and a rotary light; the buzzer and rotary light activate when gas concentrations exceed 30 ppm, while the rotary light operates when H2S concentrations are between 10-30 ppm. This system ensures safe conditions in areas with H2S gas presence. Testing involved simulating H2S gas exposure at various concentrations to assess the detector's responsiveness. Results show the developed device effectively detects H2S gas. This microcontroller-based H2S gas detector with SMS gateway is expected to be widely used in industries and environments for safety and air quality.